La recolocación de monumentos dentro del juego de pelota como mecanismo de activación ritual durante el periodo Clásico maya - Octavio Quetzalcóatl Esparza Olguín; Rogelio Valencia Rivera (Journal de la Société des Américanistes)
The monument relocation phenomenon during Prehispanic times in the Maya area, which includes engraved and plain elements, has been documented by various researchers since the realization of the very first archaeological excavations, such as those made during the last century at Tikal, Cobá, and La Milpa. This use of the stone monuments might have served many and varied purposes, but in certain contexts it certainly had a predetermined goal. Such is the case of the monuments recently found at the Maya site of Chactún, discovered in 2013, and located in the Northern sector of the Calakmul Biosphere reserve, as some of them have been found sawn and relocated into two of the ballcourts discovered so far at the site. The reuse of stelae, located at special positions inside this architectonic context, mainly at the corners of the ballcourts and visible to the spectator, indicates that this relocation did not have a random or economical reason, such as reuse of these highly valuable materials as simple construction elements. In the case of Chactún, as well as in similar contexts at other sites such as Calakmul, we propose that this phenomenon had other connotative goals, that went from a practical use of the monuments as ballcourt markers, as they were placed in the corners and at the center of the court, to a ceremonial purpose where the power and prestige of the monuments were taken to be transferred to the newly constructed ballcourt, as part of an apotropaic activation ritual that enabled this constructed space for the practice of the very special ritual activities planned for it.